Износ алмаза при шлифовании - Кузей, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The wear of natural diamond has been investigated on polishing using scanning and atomicpowered electron microscopic methods. The diamond wear is shown to proceed during destructing
the microrelief of a surface defective layer with formation of 5-40 nm size particles.